Inspiring art pieces and legendary stories for cancer patients and medical staff: experience from a single institution - Lavender Christopher (Visualized Cancer Medicine, 2024)
Art therapy has gained recognition as a valuable approach to supporting cancer patients, contributing to the reduction of depressive symptoms and pain in many hospitals worldwide. However, incorporating artworks into hospital environments can be challenging, as these spaces are primarily designed with a focus on clinical services. In this article, we present the experience of a single institution, Sun Yat-sen University Cancer Center (SYSUCC), where two artworks pay homage to the legacy of Dr. Malcolm J. Simons. Dr. Simons was renowned as a “junk DNA genius”, who dedicated his career to human genetic data analyses and made groundbreaking discoveries regarding the correlation between human leukocyte antigen genes and the incidence of nasopharyngeal carcinoma. The artworks, skillfully crafted by Dr. Simons’ wife, Ann Abrahamsen, provide solace and healing for the many patients and family members that cross their path daily in SYSUCC. Promoting healing and well-being, they offer a short respite from the uncertainty for patients and loved ones undergoing cancer treatment.